Pengembangan desain formular kelayakan isolasi mandiri di rumah bagi pasien COVID-19 untuk mendukung surveilans epidemiologi di DI Yogyakarta - Anton Kristijono; Niko Tesni Saputro (Jurnal Kesehatan Pengabdian Masyarakat (JKPM), 2021)
The Ministry of Health revealed that the stigma and negative stereotypes given by individuals or community groups towards health workers or COVID-19 patients contributed to the high mortality rate due to the corona virus. Stigma will lead to marginalization, and worsen health status and cure rates, in this case stigma contributes to high mortality rates, when people exposed to COVID-19 must self-isolate at home. The purpose of this community service is to develop a design for a self-isolation eligibility form at home for COVID-19 patients to support epidemiological surveillance at the Tempel 1 Health Center, Sleman. The service method is carried out in stages: (1) FGD to equalize perceptions and identify data needs and information on the feasibility of self-isolation at home for COVID-19 patients without symptoms or with mild symptoms, (2) design form, (3) socialization of form design and (4) evaluation of implementation (input, process, and output) as well as recommendations in the form of form design results. It is recommended that the design of the resulting form is part of the recording and reporting of Covid-19 epidemiological surveillance at primary health facilities, and as a guide for primary health care workers to recommend that Covid 19 patients in their work areas can self-isolate at home or not. The targets consisted of epidemiological surveillance officers, Health Promotion officers, Medical Records and Health Information (RMIK) officers and community leaders. The results of the service are in the form of 4 form designs, namely: (1) Self-Isolation Eligibility Form at home for COVID-19 patients without symptoms or with mild symptoms to support epidemiological surveillance at the Tempel 1 Health Center Sleman (Form 1A.2021.rev0), (2) Forms Self-Isolating Home Information (Form 1B.2021.rev0), (3) Contact History List Form (Form 1C.2021.rev0) and (4) Monitoring Form (Form 2A.2021.rev0).